Recurrent Hyperkalaemia due to Selective Aldosterone Deficiency: Correction by Angiotensin Infusion. Issue 5854 (17th March 1973) - Brown, J. J.; Chinn, R. H.; Fraser, R.; Lever, A. F.; Morton, J. J.; Robertson, J. I. S.; Tree, M.; Waite, M. A.; Park, D. M.
Abstract : A patient with recurrent weakness and blurring of consciousness associated with hyperkalaemia due to aldosterone deficiency is reported. The plasma concentrations of renin, angiotensin II, and aldosterone were low and did not increase during sodium deprivation. Blood angiotensin I was also low while renin-substrate concentration was normal. Infusion of angiotensin produced a distinct rise in plasma aldosterone. The patient was treated successfully with fludrocortisol. The results support the concept that the renin-angiotensin system is an important regulator of aldosterone secretion and that in the syndrome of acquired selective hypoaldosteronism the primary abnormality may be a deficiency of renin. It is suggested that a selective lack of aldosterone should be considered in all cases of otherwise unexplained hyperkalaemia.